Multi-level magnetic RAM using domain wall shift for energy-efficient, high-density caches - Sharad, Mrigank; Venkatesan, Rangharajan; Raghunathan, Anand; Roy, Kaushik (Proceedings of the 2013 International Symposium on Low Power Electronics and Design, 2013)
Spin-based devices promise to revolutionize computing platforms by enabling high-density, low-leakage memories. However, stringent tradeoffs between critical design metrics such as read and write stability, reliability, density, performance and energy-efficiency limit the efficiency of conventional spin-transfer- torque devices and bit-cells. We propose a new multi-level cell design with domain wall magnets (DWM-MLC) that significantly improves upon the read/write performance, density, and write energy consumption of conventional spin memories. The fundamental design tradeoff between read and write operations are addressed in DWM-MLC by decoupling the read and write paths, thereby allowing separate optimization for reads and writes. A thicker tunneling oxide is used for higher readability, while a domain-wall-shift (DWS) based write mechanism is used to improve write speed and energy. The storage of multiple bits per cell and the ability to use smaller transistors lead to a net improvement in density compared to conventional spin memories. We perform a systematic evaluation of DWM-MLC at different levels of design abstraction. At the circuit level, DWM-MLC achieves 2X improvement in density, read energy and read latency over its 1-bit counterpart. We evaluate an "all-spin" cache hierarchy that uses DWM-MLC for both L1 and L2, resulting in 4.4X (1.7X) area improvement and 10X (2X) energy reduction at isoperformance over SRAM (STT-MRAM).